An In-Vivo Study of Effects of Platelet-Rich Plasma on Transforming Growth Factor-β1 and Matrix Metalloprotein 9 Expression in Traumatic Ulcers with Diabetes Mellitus - Radithia, Desiana; Yuliana, Yuliana; Puspitasari, Yeni; Sismiyanti, Rossy; Pratiwi, Aulya Setyo (European Journal of Dentistry, 2023)
Objective Diabetes mellitus is not only characterized by alterations in the wound healing process but also during oral ulcer healing. The platelet-rich plasma (PRP) can be used to stimulate the healing process. This study was performed to analyze the effect of PRP on traumatic ulcers with diabetes mellitus in an animal model by analyzing the expression of transforming growth factor β1 (TGF-β1) and matrix metalloprotein 9 (MMP-9).Materials and Methods The diabetes mellitus model was developed using streptozotocin that was administrated to Rattus novergicus. The traumatic ulcer model was obtained by placing a heated tip of a ball burnisher for 5 seconds on the lower mucosa labial. Then, the traumatic ulcer was treated with PRP for 3, 5, and 7 days. The expression of TGF-β1 and MMP-9 was analyzed with indirect immunohistochemistry, and differences between each marker were analyzed with statistical analysis.Results All animals showed clinical oral ulceration as a yellow base during the experiment. The application of PRP showed a higher level of TGF-β1 expression than the controls for 3, 5, and 7 days (p < 0.05). In contrast, the MMP-9 expression was lower than the control for 5 and 7 days (p < 0.05).Conclusion The PRP affected traumatic ulcers with diabetes mellitus by promoting healing through TGF-β1 expression and suppressing the MMP-9 expression. This material can serve to develop a promising topical therapy for traumatic ulcers, especially with an underlying disease such as diabetes mellitus.
Keywords: diabetes mellitus; oral ulcer; platelet-rich plasma; TGF-β1; MMP-9